Comparison sea and rail transport of container - Bínová, Helena; Březina, Edvard; Mráček, Vladimír (University of Pardubice, 2018)
Container transport of goods between China and Europe, respectively between China and the Czech Republic, is an important part of trade between these countries and its volume is still increasing. This contribution contains analysis of the current state of two modes of transport, namely maritime and rail transport between the Far East and Europe, respectively between the Far East and the Czech Republic. Both of these modes of transport are environmentally friendly and should be used for transport of goods in the future. One part of this contribution contains comparison of selected aspects. Selected aspects are prices, time of transport and safety. Comparison of the two modes, maritime and rail transport is reasonable, because prices, time of transport and safety are important for a decision, which mode of transport to use.
Keywords: maritime transport; railways; environment; safety; container